Identifikasi Genotype Rumah Adat Sumba Barat dengan Metode Space Syntax - Irfan Irwanuddin (RUAS (Review of Urbanism and Architectural Studies), 2018)
Various influences toward West Sumba traditional house’s morphology are affecting the way its exterior appearance has formed. Despite their exterior uniformity, each of these houses is showing different spatial configuration. Spatial configuration is a product of certain social processes. In other words, different society will produce different spatial configuration. Meanwhile, it is believed that space syntax method could be employed to elaborate objectively particular social phenomenon by examining its spatial configuration. Based on that, this research attempted to identify the genotype in those houses to reveal the social phenomenon occurred. Core and territory are parts of several factors that potentially represent a cultural pattern in certain society. The result revealed that these houses are in fact sharing same spatial patterns. It is strongly indicated by core and territory pattern comparison. Four of the five samples are showing a strong genotype, while the left one is showing a genotype differences. In addition, there is a fact that this house with different genotype is located in a village that exposed to modernization.